What parents still do not know about No Child Left Behind and why it matters. Issue 3 (3rd May 2016) - Lavery, Lesley E.
Abstract: Utilizing data from an original survey of public school parents, I examine the depth and distribution of parents' knowledge of No Child Left Behind (NCLB). A close exploration of parents' NCLB knowledge, policy-based experiences, and policy evaluations suggests that a superficial policy understanding may contribute to low uptake of policy-related opportunities and the lack of organized political response to perceived policy pitfalls. Though several other policy initiatives have now been layered atop this particular legislative act, given the policy's reach and scope, and reliance on parents' participation, a more careful understanding of NCLB's effects also suggests how future policy reforms might be tailored to better encourage parent awareness of and participation in the school improvement process.